1995
DOI: 10.2466/pr0.1995.77.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Preschool Experiences of Advantaged Children

Abstract: Experiences of advantaged children were examined among 85 kindergarten, 72 first-grade, 61 second-grade, and 66 third-grade boys and girls. Preschool and nonpreschool/nonday-care groups scored significantly higher on academic self-esteem than a day-care group. The preschool group scored higher on CTBS Mathematics than the other two groups, and the preschool and day-care groups had significantly fewer absences in public school than the nonpreschool/nonday-care group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Similar to teacher ethnicity, the context from which children are transitioning may also help (or hinder) children's adjustment and school success. For instance, Warash and Markstrom-Adams (1995) found that children who transitioned from a center-based educational program had an advantage compared with children who transitioned from other types of child care as evidenced by higher academic self-esteem and mathematics scores. Growing evidence indicates that children tend to have better academic skills if they attend center-based care (Fantuzzo et al, 2005;Huston et al, 2003;National Institute of Child Health and Human Development Early Child Care Research Network, 2001;Schweinhart, Barnes, & Weikart, 1993;Sylva & Wiltshire, 1994), and especially if they attend publicly financed prekindergarten programs (Gormley, Gayer, Phillips, & Dawson, 2005;Magnuson, Ruhm, & Waldfogel, 2004).…”
Section: Teacher Race/ethnicity and Center-based Experience Prior To mentioning
confidence: 99%
“…Similar to teacher ethnicity, the context from which children are transitioning may also help (or hinder) children's adjustment and school success. For instance, Warash and Markstrom-Adams (1995) found that children who transitioned from a center-based educational program had an advantage compared with children who transitioned from other types of child care as evidenced by higher academic self-esteem and mathematics scores. Growing evidence indicates that children tend to have better academic skills if they attend center-based care (Fantuzzo et al, 2005;Huston et al, 2003;National Institute of Child Health and Human Development Early Child Care Research Network, 2001;Schweinhart, Barnes, & Weikart, 1993;Sylva & Wiltshire, 1994), and especially if they attend publicly financed prekindergarten programs (Gormley, Gayer, Phillips, & Dawson, 2005;Magnuson, Ruhm, & Waldfogel, 2004).…”
Section: Teacher Race/ethnicity and Center-based Experience Prior To mentioning
confidence: 99%